AFFORDANCE BASED FRAMEWORK OF HUMAN PROBLEM SOLVING: A NONREPRESENTATIONAL ALTERNATIVE - SINGH, Pankaj (Studia Universitatis Babeș-Bolyai Philosophia, 2021)
Problem solving is a crucial higher-order thinking ability of humans. Humans’ ability to solve problems is a critical higher-order thinking ability. Mathematical problem solving, analogical problem solving, complex problem solving, situated problem solving, and so on are all examples of problem solving. Furthermore, distinct types of research analysis, models, and theories are based on the mechanisms and elements involved in diverse problem-solving types. The conventional approach to understanding human problem solving is a representation-laden description, which is similar to most cognitive explanations of psychological processes. On the other hand, the paper goes beyond representational theories and models to investigate nonrepresentational and situated aspects of human problem solving. Problem solving is a crucial higher-order thinking ability of humans. The paper is a rudimentary attempt to present a nonrepresentational, Affordance-Situation-Attunement (ASA) framework of human problem solving. The aim is to invoke ASA as an alternative framework, in contrast with the dominant representational explanation of human problem solving. The aim is not to disparage the representational theories and models of problem solving but to contribute a nonrepresentational working framework and elements for highlighting the situated nature of human problem solving.